Stochastic Ferromagnetism : analysis and numerics - Baňas, Lubomír (De Gruyter studies in mathematics, 2014)
This monograph examines magnetization dynamics at elevated temperatures which can be described by the stochastic Landau-Lifshitz-Gilbert equation (SLLG). Comparative computational studies with the stochastic model are included. Constructive tools such as e.g. finite element methods are used to derive the theoretical results, which are then used for computational studies.